2011
DOI: 10.1371/journal.pone.0019278
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide DNA Methylation Analysis Reveals Phytoestrogen Modification of Promoter Methylation Patterns during Embryonic Stem Cell Differentiation

Abstract: BackgroundEnvironmental challenges during development affect the fetal epigenome, but the period(s) vulnerable to epigenetic dysregulation is(are) not clear. By employing a soy phytoestrogen, genistein, that is known to alter the epigenetic states of the Avy allele during embryogenesis, we have explored the sensitive period for epigenetic regulation. The post-implantation period, when de novo DNA methylation actively proceeds, is amenable to in vitro analysis using a mouse embryonic stem (ES) cell differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 24 publications
3
15
0
1
Order By: Relevance
“…165 The validated and widely used ES cell test for toxicity 166,167 demonstrated that exposure to BPA or genistein significantly altered genome-wide methylation patterns and decreased ES cell-to-cardiomyocyte differentiation. 168,169 Furthermore, the combination of BPA and genistein had a synergistic effect at lower concentrations, similar to those observed in human blood or sera. 168 …”
Section: Dietary Exposures and Supplementssupporting
confidence: 65%
“…165 The validated and widely used ES cell test for toxicity 166,167 demonstrated that exposure to BPA or genistein significantly altered genome-wide methylation patterns and decreased ES cell-to-cardiomyocyte differentiation. 168,169 Furthermore, the combination of BPA and genistein had a synergistic effect at lower concentrations, similar to those observed in human blood or sera. 168 …”
Section: Dietary Exposures and Supplementssupporting
confidence: 65%
“…However, it is also true that DNA methylation patterns established around implantation can be modified by further methylation or demethylation during subsequent stages of organogenesis as a result of environment factors that are not yet well known. An illustrative example is the effect of the phytoestrogen genistein, which has been described to mediate global changes in DNA methylation levels during mouse embryonic stem cell differentiation in the post gastrulation period but before germ layer differentiation (Sato et al, 2011). Genistein-induced epigenetic alterations seems to share important similarities with those found in intrauterine growth retardation neonates (Einstein et al, 2010), but the magnitude is markedly lower than the differences found between tissues or in cancer.…”
Section: Perinatal Events (Gestation and Lactation)mentioning
confidence: 99%
“…Recently, genistein and daidzein have been shown to induce DNA demethylation in the promoter regions of BRCA1, GSTP1, EPHB2 and RASSF1A in human prostate cancer cell lines [86]. Genistein has also been shown to interfere with DNA methylation in differentiated ES cells after the process of de novo methylation [87]. In endometrial stromal cells genistein has been shown to promote DNA demethylation of the steroidogenic factor 1 (SF-1) promoter [88].…”
Section: Environmental Epigeneticsmentioning
confidence: 99%